Analysis Of Phytochemical Profile And Antioxidant Activities From Ethanol Extract Of Leaf, Stem Bark And Wood Clausena lansium L. - Fajar Fauzi Abdullah; Ruchiyat Ruchiyat; Iqbal Musthapa (Jurnal Kartika Kimia, 2020)
Wampi belongs to Rutaceae family. The shape of this plant is kind of bush or small tree and its fruits are similar to grapples or oranges. C. lansium was reported has the main biological activity as radical scavenger. The aim of this study to identify the content of secondary metabolites found in bark, woody stems and leaves of C. lansium plants, and to determine antioxidant activity through IC50 values. This research method begins with sample preparation, plant determination, simplicia characteristic examination, extraction, characterization with infrared spectroscopy, thin layer chromatography (TLC), then proceed with antioxidant activity assay using DPPH method (2.2 -Diphenyl-1-picrylhidrazyl) with a comparison of vitamin C. The results of this study showed that C. lansium contains alkaloids and kumarin. Furthermore, antioxidant activity assay measured absorption at a wavelength of 517 nm, obtained IC50 values ​​of vitamin C 6.22 ppm; bark 231.54 ppm (weak), wood stem 131.49 ppm (weak), and leaves 22,60 ppm (strong). Keywords: Clausena lansium, Antioxidant, phytochemical profile.